The Role of Parenting in Supporting Early Childhood Emotional Development - fiyaa, lutfiyah Azarah; Uke maharani Dewi; Annif Munjidah; Hinda Noviyanti; Umik Rowaikhan; Masita, Elly Dwi (Universitas Nahdlatul Ulama Surabaya, 2025)
Parenting plays an important role in early childhood emotional development. This study aims to measure the effectiveness of parenting education on changes in parenting styles and its impact on children's emotions. Using a quantitative approach with a quasi-experiment one group pretest-posttest design, the intervention was given to 20 parents in Wage Village, Sidoarjo, in the form of short counseling lasting approximately 20 minutes. Data analysis was carried out by paired sample t-test. The results showed a significant decrease in authoritarian parenting and an increase in democratic parenting tendencies. In addition, there was a significant decrease in children's emotional, behavioral, and hyperactivity problems (p < 0.05). However, peer relationships and prosocial behavior did not show significant changes. Parenting education has been shown to be effective in improving parenting patterns and supporting early childhood emotional regulation.